A Model Of Fiqh Al-Ṭahārah For The Indigenous Muslim Community In Malaysia: A Fuzzy Delphi Application On The Issue Of Food Containers And Kitchen Utensils Contaminated By Najāsah Al-Khinzīr - Paiz Hassan; Mohd Anuar Ramli; Zulkefli Aini; Muhammad Yusri Yusof @ Salleh; Muhd Imran Abd Razak; Mohd Zahirwan Halim Zainal Abidin; Muhammad Syazwan Faiz Shahrom (Universiti Sains Islam Malaysia, 2025)
Journal of Fatwa Management and Research, Volume 30 Issue 3 Page (81-96)